OPTIMIZATION OF GELATIN CONCENTRATION IN TABLET WITH AFRICAN LEAF EXTRACT (Vernonia Amygdalina) - Wahlanto, Panji; Yusuf, Anna L; Nugraha, Davit; Siti Rahmah KR; Dissya Alifia (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
African plants, especially the leaves, are a type of medicinal plant used by the community. This African leaf contains active lavonoids that can be used to measure blood glucose levels. Tablet preparations have the advantage that they are easy to consume, so in this study African leaves (Vernonia Amygdalina) were made into tablets. The ratios of the binder used were 4%, 5%, and 6%. After obtaining the evaluation results, data analysis was performed using the Kruskal–Wallis SPSS statistical test with a confidence level of 95%. The evaluation results showed that the three formulations only fulfilled the respective requirements, namely for the angle of repose test between 16.6° - 21.3°, the granule thickening test of all formulations is below <20% and meets the requirements, the weight uniformity test has an average of 191-192 mg meeting the predetermined requirements, namely not more than 3 times with an average of 7.35 -7.36 mm and a thickness of mean + SD 0,47 the disintegration time test of all formulations stated that they met the requirements that had been determined that is not more than 15 minutes, the friability test only on formulation III which met the requirements to get a result of 0.54% in formulations I and II did not meet the specified requirements, the hardness test of all formulations did not meet the specified test requirements. Keywords: African leaf extract, gelatin, tablets.